Analysis of Project Performance and the Selection of Mitigation Strategies for Fiscal Disruptions Due to Government Budget Relaxation Policies - Aristo Yonghy Robertus; Bambang Endro Yuwono (Green Publisher Indonesia, 2026)
Changes in budget allocation mechanisms and delays in fund disbursement have adversely affected project schedules, cost efficiency, and cash flow stability. This study aims to quantitatively evaluate the impact of fiscal disruption on project performance using Earned Value Management (EVM) indicators—namely the Schedule Performance Index (SPI) and Cost Performance Index (CPI)—and to identify the most feasible managerial mitigation strategy under constrained fiscal conditions. The research adopts a quantitative-dominant mixed-methods approach utilizing secondary data derived from official project documents, including S-curves, progress reports, cash flow statements, and government fiscal policy regulations. Project performance is assessed through EVM, while financial conditions are evaluated using Net Cash Flow (NCF) and Net Profit (NP) analysis. Several alternative funding strategies are analyzed using Discounted Cash Flow (DCF) techniques such as Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback Period (DPP), and Debt Service Coverage Ratio (DSCR). The alternatives are subsequently ranked using a Multi-Criteria Decision Making (MCDM) approach based on a Weighted Scoring Model (WSM). The results indicate that fiscal adjustment policies significantly deteriorated project performance, as reflected by an SPI of 0.669 and a CPI of 0.957 as of June 2025. Among the evaluated mitigation strategies—internal funding, external funding, partial PPP, and a combination of internal–external funding—the combined strategy yields the most balanced technical and financial performance. Although it does not generate the highest profit, this strategy demonstrates superior overall feasibility and resilience under fiscal pressure.